Do on call Neurosurgery Residents Interpret Cranial CT Scans in Trauma Patients Accurately? A Cross-Sectional Study - Muhammad Mehboob Alam, Aanab Hayat, Aziz ur Rehman, Afreen Anjum, Naveeda Rauf, Muhammad Saeed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Traumatic brain injury (TBI) is a major public health concern, requiring timely and accurate interpretation of cranial computed tomography (CT) scans for optimal management. Neurosurgery residents often provide initial assessments of these scans in emergency settings. However, the concordance between their interpretations and those of consultant radiologists remains a critical factor in ensuring accurate diagnosis and treatment decisions. Objective: This study aimed to evaluate the accuracy of on-call neurosurgery residents in interpreting cranial CT scans in trauma patients by assessing the level of concordance with consultant radiologists. Methods: A prospective cross-sectional study was conducted at Aga Khan University Hospital, during the period of one year from July 2021 to June 2022, including 194 patients with TBI who underwent unenhanced cranial CT scans. Neurosurgery residents’ interpretations were compared with consultant radiologists’ reports using the kappa test to measure concordance. Discordance was categorized as minor (differences in subtle findings) or major (misclassification of critical abnormalities). Data analysis was performed using SPSS version 19. Results: Complete concordance between neurosurgery residents and radiologists was observed in 58.8% of cases, with an overall kappa value of 0.97 (p < 0.001), indicating near-perfect agreement. Minor discordance occurred in 32.5% of cases, while major discordance was found in 8.8%. Concordance improved with resident seniority, demonstrating enhanced accuracy with increasing training levels. Conclusion: While neurosurgery residents exhibit a high degree of accuracy in interpreting cranial CT scans, notable discordance persists, particularly in subtle findings. Structured training programs, standardized reporting protocols, and AI-assisted interpretation tools can further enhance diagnostic accuracy, ultimately improving patient outcomes in emergency neuroimaging. Keywords: Neurosurgery residents, cranial CT interpretation, traumatic brain injury, diagnostic accuracy